CNN – Business Day: George Soros on Russian Referendum
CNN business magazine with anchors Deborah Marchini and Stuart Varney. Topics covered: financial markets throughout the world; stock markets in the U.K., healthcare reform in the U.S.; IMF and international investments; Russia’s economic reforms and referendum; economic sanctions in former Yugoslavia; Japan’s currency and the fate of its corporations; IBM and technological developments. The program features an interview with George Soros on the Russian referendum.